KNOWLEDGE, ATTITUDE AND PRACTICES OF HEALTH STAFF REGARDING INFECTIOUS WASTE HANDLING OF TERTIARY CARE HEALTH FACILITIES AT METROPOLITAN CITY OF PAKISTAN - Kumar, Ramesh; Samrongthong, Ratana; Shaikh, Babar Tasneem (Journal of Ayub Medical College Abbottabad, 2013)
Background: Health Care Waste (HCW) is considered as the second dangerous waste in the World that needs to be properly disposed by trained health care staff. Good knowledge, positive attitude and safe practices of medical staff is very imperative while managing this infectious waste. This assessment has been conducted to determine the situation and KAP of infectious waste management in health care workers working at tertiary care settings health facilities of Rawalpindi, Pakistan. Methods: This study was part of an ongoing quasi-experimental with control and intervention design and was conducted in tertiary care governmental hospitals of Rawalpindi by interviewing healthcare workers (HCWs) who were selected randomly after the sample size calculation. The participants were selected according to the proportional size of the each HCWs for their equal representation from all the groups. Self-administered valid and reliable questionnaire were adapted after taking the written consent. Ethical consideration was taken from ethical committee of Health Services Academy Pakistan. Results: Total 275 HCWs including doctors, nurses, paramedics and sanitary workers were interviewed during this baseline survey. The mean age of the health workers were 30±5 years. Infectious waste management practices with in both hospitals were not found statistically significant (p=0.33). However, the socio-demographic information like age, gender, level of education and experience, when compared with the practices were found statistically significant (p<0.05). Doctors and nurses have better knowledge, positive attitude and good practices compare to paramedics and sanitary staff regarding infectious waste management and was found statistically significant (p<0.05). Conclusions: Practices among HCWs were not found up to the standards in these tertiary care hospitals ofPakistan and were not following the proper guidelines and WHO rules. Keywords: Health Care Workers, Waste Management, Infectious Waste, KAP, Assessment